A GEOPHYSICAL DATA INTERPRETATION METHOD FOR THE RECONSTRUCTION OF THE STRESSED-STRAINED STATE OF A ROCK MASSIF - Nazarov L.A.; Nazarova L.A. (My University, 2004)
The GPS net has been rapidly developing in the last decade. The number of observation points is increasing, and the equipment is becoming simpler and less expensive. The software for initial processing of data is being refined for more precise determination of the geographical coordinates of objects. In particular, the information that is obtained is used by geophysicists to monitor seismotectonic processes in the upper part of the Earth's crust. The analysis is usually reduced to the calculation of relative distances between the observation points with further integral estimate of deformations in specific regions of the study area. Structural and physical properties are commonly not taken into account. However, satellite geodesy data also include geomechanical information, the majority of which is lost in the implementation of the existing methods of interpreting them. In this, article we suggest a method for determining boundary conditions on the basis of displacements specified over a discrete multitude of inner points in the study region, which allows us to calculate the stress-strain fields. Although the GPS data are recorded at a daytime surface usually modeled as a plane, the solution is obtained in the more general 3D approach.